Enzyme-instructed morphological transition of the supramolecular assemblies of branched peptides - Yang, Dongsik; He, Hongjian; Xu, Bing (Beilstein Journal of Organic Chemistry, 2020)
Here, we report the use of an enzymatic reaction to cleave the branch off branched peptides for inducing the morphological transition of the assemblies of the peptides. The attachment of DEDDDLLI sequences to the ε-amine of the lysine residue of a tetrapeptide produces branched peptides that form micelles. Upon the proteolytic cleavage of the branch, catalyzed by proteinase K, the micelles turn into nanofibers. We also found that the acetylation of the N-terminal of the branch increased the stability of the branched peptides. Moreover, these branched peptides facilitate the delivery of the proteins into cells. This work contributes insights for the development of peptide supramolecular assemblies via enzymatic noncovalent synthesis in cellular environment.
Keywords: acetylation; branched peptides; enzyme; nanostructures; N-terminal; responsive; self-assembly